(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
The article focuses on defining indications for surgical treatment in acute pancreatitis, taking into account the severity of the disease and ensuring adequate protein-energy balance. Indications for surgical intervention in the early and late stages of the disease, criteria for predicting the severity of the pathological process, and patient nutritional support programs are discussed. It is shown that timely determination of surgical tactics and rational protein-energy support contribute to reducing complications and improving treatment outcomes.